Earlier and lower dose administration of sugammadex: A randomised placebo-controlled trial. Issue 8 (August 2021) - Duranteau, Olivier; Fernandez, Wendy; Tuna, Turgay; Engelman, Edgard; Van Obbergh, Luc; Tabolcea, Ionut
Abstract : BACKGROUND: Sugammadex allows for rapid reversal of muscle relaxation after the use of rocuronium or vecuronium. The lowest recommended dose is 2 mg kg −1 intravenously when there are two twitches during the train-of-four stimulation. OBJECTIVE: To study the efficacy and risks of a lower dose of sugammadex administered earlier. DESIGN: Monocentric randomised controlled double-blind study. SETTING: Academic hospital. PATIENTS: Eighty patients were enrolled and randomised in 8 groups of 10 patients, 56 were finally evaluated. INTERVENTIONS: Patients were distributed in two clusters constituting four groups each. In the first cluster, injections were administered after the return of one twitch with the train-of-four (TOF1). In the second cluster, injections were delivered after the return of two twitches with the TOF (TOF2). We created four groups in each cluster for different dosages: placebo, 0.5, 1 or 2 mg kg −1 . MAIN OUTCOME MEASURES: Time between the injection of sugammadex and full recovery (TOF ratio > 0.9) that is expressed in minutes. RESULTS: Fifty-six successive patients were assessed between February and August 2018. The difference to TOF greater than 0.9 was not statistically significant between groups with the same dose administered at different times ( F value = 0.001, P value = 0.975). There was a significant difference between groups with a different dosage administered at the same time ( F ratio = 28.34; P value <0.0001). Concerning the time to TOF greater than 0.9 from the time point of TOF1, the timing of the dosages were statistically significant using log rank test ( P < 0.0001). No patient presented a reparalysis. CONCLUSION: No difference between injecting sugammadex at TOF1 or TOF2 was found regarding time to full recovery. Difference regarding sugammadex quantity was found and compatible with other studies. TRIAL REGISTRATION: clinicaltrials.gov: 'BRIDION_ERASME', EudraCT: 2017-005074-19.